2023
DOI: 10.1073/pnas.2212338120
|View full text |Cite
|
Sign up to set email alerts
|

A selective inhibitor of the sperm-specific potassium channel SLO3 impairs human sperm function

Abstract: To fertilize an oocyte, the membrane potential of both mouse and human sperm must hyperpolarize (become more negative inside). Determining the molecular mechanisms underlying this hyperpolarization is vital for developing new contraceptive methods and detecting causes of idiopathic male infertility. In mouse sperm, hyperpolarization is caused by activation of the sperm-specific potassium (K + ) channel SLO3 [C. M. Santi  et al. ,  FEBS Lett. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…The SLO3 K + channel has previously been shown to be essential for mediating the hyperpolarization observed in capacitated mouse sperm [ 56 ]. A recent study utilized a novel specific inhibitor of the human SLO3 K + channel, VU0546110, that prevented human sperm from hyperpolarizing and undergoing hyperactivated activity, and prevented the Ca 2+ - or progesterone-induced acrosome reaction [ 57 ]. Interestingly, a study using human sperm found no evidence of alkalization of either the sperm head or flagellum in response to valinomycin-induced hyperpolarization [ 26 ], suggesting a potential different role of NHE10 and/or NHE11 in human sperm as compared to sea urchin sperm, in which the suSLC9C protein was shown to be responsible for the hyperpolarization-evoked alkalization in response to speract stimulation [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The SLO3 K + channel has previously been shown to be essential for mediating the hyperpolarization observed in capacitated mouse sperm [ 56 ]. A recent study utilized a novel specific inhibitor of the human SLO3 K + channel, VU0546110, that prevented human sperm from hyperpolarizing and undergoing hyperactivated activity, and prevented the Ca 2+ - or progesterone-induced acrosome reaction [ 57 ]. Interestingly, a study using human sperm found no evidence of alkalization of either the sperm head or flagellum in response to valinomycin-induced hyperpolarization [ 26 ], suggesting a potential different role of NHE10 and/or NHE11 in human sperm as compared to sea urchin sperm, in which the suSLC9C protein was shown to be responsible for the hyperpolarization-evoked alkalization in response to speract stimulation [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…This work represents the first version of the STB. Future revisions could contain newly published compounds modulating functions in spermatozoa e.g., a sAC inhibitor TDI-11861 (Balbach et al, 2023), a CatSper inhibitor RU1968 (Schierling et al, 2023), a SLO3 inhibitor (Lyon et al, 2023) or other contributions from the research community. In addition, the STB could present an important resource for testing and benchmarking newly developed drug screening assay.…”
Section: Mainmentioning
confidence: 99%
“…Only in the last 5 y have a handful of potential drugs emerged, such as EP055 against EPPIN ( 1 ), CDD-1102 against BRDT ( 2 ), triptonide against JUP/SPEM1 ( 3 ), and YCT529 against RARA ( 4 ). Now, a new molecule has been added to this short list: VU0546110 ( 5 ), a small molecule that inhibits Slowpoke Homolog 3 (SLO3), an ion channel specific to sperm. Because SLO3 channels are absent from women ( 6 ), they have the added benefit of being targetable by nonhormonal unisex contraceptives and, therefore, have an easier regulatory pathway to market.…”
mentioning
confidence: 99%
“…Lyon et al. ( 5 ) identify VU0546110, a potent small-molecule inhibitor of SLO3, through screening of a chemical library of 50,240 compounds ( 5 ). They show that VU0546110 exerts its effect on human sperm by blocking SLO3 and inhibiting hyperpolarization ( 5 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation